2011
DOI: 10.1111/j.1461-0248.2011.01721.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal legacies: transgenerational effects of temperature on growth in a vertebrate

Abstract: Transgenerational plasticity (TGP), a generalisation of more widely studied maternal effects, occurs whenever environmental cues experienced by either parent prior to fertilisation results in a modification of offspring reaction norms. Such effects have been observed in many traits across many species. Despite enormous potential importance-particularly in an era of rapid climate change-TGP in thermal growth physiology has never been demonstrated for vertebrates. We provide the first evidence for thermal TGP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
324
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(339 citation statements)
references
References 52 publications
12
324
3
Order By: Relevance
“…1). The 116 high proportion of contigs in this group with putative function in organ development (two 117 contigs; ppdpfa and ptf1a) and endothelial cell proliferation (four contigs; nlrp14 and timp2) 118 suggests that lower metabolic costs enabled these cellular processes to function at a higher 119 level in transgenerationally acclimated fish, which is consistent with acclimation of growth 120 rates in fish exposed transgenerationally to elevated temperatures 3,4 . In addition, this group 121 contains five contigs related to transcriptional regulation (three genes: rorb, ptf1a, and 122 rps27), two of which enhance expression of genes involved in organogenesis (rorb, ptf1a).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…1). The 116 high proportion of contigs in this group with putative function in organ development (two 117 contigs; ppdpfa and ptf1a) and endothelial cell proliferation (four contigs; nlrp14 and timp2) 118 suggests that lower metabolic costs enabled these cellular processes to function at a higher 119 level in transgenerationally acclimated fish, which is consistent with acclimation of growth 120 rates in fish exposed transgenerationally to elevated temperatures 3,4 . In addition, this group 121 contains five contigs related to transcriptional regulation (three genes: rorb, ptf1a, and 122 rps27), two of which enhance expression of genes involved in organogenesis (rorb, ptf1a).…”
supporting
confidence: 51%
“…Some animals have the remarkable capacity to acclimate across generations to projected 22 future climate change [1][2][3][4] ; however, the underlying molecular processes are unknown. We 23 sequenced and assembled de novo transcriptomes of adult tropical reef fish exposed 24 developmentally or transgenerationally to projected future ocean temperatures and 25 correlated the resulting expression profiles with acclimated metabolic traits from the 26 same fish.…”
mentioning
confidence: 99%
“…Epigenetic modifications of cyp19a1a were also reported during sex change in the rice field eel (66). In fish, transgenerational effects of heat exposure have been recently described (67). In the tongue sole, Cynoglossus semilaevis, which has a ZW/ZZ sex-determining system as in wild zebrafish, heat-induced neomales were responsible for the epigenetic transmission of DNA-altered states, resulting in the production of masculinized offspring even at normal temperatures (68).…”
Section: Discussionmentioning
confidence: 92%
“…There is growing awareness that such effects can contribute to adaptation in natural populations, especially when maternal and offspring environments are positively correlated (Burgess & Marshall, 2014; Dey et al., 2016; Salinas & Munch, 2012; Shama, 2015; Uller et al., 2013). For instance, Donelson, Munday, McCormick, and Pitcher (2012) found that damselfish ( Acanthochromis polyacanthus ) exposed to thermal stress produce offspring with superior thermal tolerance relative to offspring of unexposed parents.…”
Section: Discussionmentioning
confidence: 99%